FAKTOR YANG MEMENGARUHI KEPUASAN PELANGGAN DALAM LAYANAN RIDE HAILING DI INDONESIA - Ichsan Salim; Renee Ricardo; Syaiful Bahri MZ; Tanty Marisa (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The use of technology in these services has significantly become an important part of people's daily lives. The ease of using ride-hailing services makes the adoption of this service easier to accept and use. The purpose of this study was to investigate the factors influencing customer satisfaction in using online-based ride-hailing services in the sharing economy of business platforms in Indonesia. This study empirically analyzed variable data using non-probability sampling techniques on a questionnaire to 500 sample data from respondents who have used online-based four-wheeled car transportation with a frequency of more than five times a year. The linear regression analysis model is used to examine the effect of 7 variables affecting Indonesia's customer satisfaction. Based on the results, four variables significantly influenced customer satisfaction: tangibility, reliability, responsiveness, and information and communication technology (ICT). The variable that affected but was not significant (marginally significant) was the price, and two variables that did not affect customer satisfaction were assurance and empathy. Thus, ride-hailing service providers need to maintain service quality standards to ensure customer satisfaction. This research is also useful for ride-hailing services to maintain fairness in prices, pay attention to the ease of use of information and communication technology, and maintain customer satisfaction to increase competitive advantage over competitors. Keywords: customer satisfaction, ICT, price, Ride hailing, service quality